Vertically Exported Phytoplankton (< 20 µm) and Their Correlation Network With Bacterioplankton Along a Deep-Sea Seamount - Zhao, Hanshuang; Zhang, Zenghu; Nair, Shailesh; Zhao, Jiulong; Mou, Shanli; Xu, Kuidong; Zhang, Yongyu (Frontiers in Marine Science, 2022)
Phytoplankton have been observed to be widely distributed in the oceanic vertical water columns and have an important contribution to carbon sequestration via biological pump mechanism. However, in seamount areas with strong hydrodynamics, their vertical export is still unclear. Moreover, considering phyto- and bacterioplankton are inseparable in the ocean, their correlation in the water columns is also an important scientific issue to be understood, which is related to the microbial ecological process in the aphotic zone. Here, we revealed that there were various phytoplankton (< 20 µm) along a deep-sea seamount (M5 seamount) in the Western Pacific Ocean, and their molecular community structures had no significant difference in different water layers, which were all dominated by Dinophyceae, Syndiniales, and Baciilariophyta. In contrast, the vertical distribution of bacterioplankton community structure showed great variation. Notably, distinct species-specific algae-bacteria relationships occurred in different water layers, and relatively more prominent algae-bacteria relationships occurred in the mesopelagic and bathypelagic zones than the euphotic zone. In laboratory experiments, after co-cultivating the significantly different bacterial communities from different water layers with Synechococcus sp. PCC7002 and Phaeodactylum tricornutum CCMP2561, respectively, the distinct bacterial community structures from different water layers turned similar, reflecting the strong reshaping effect of phytoplankton on the structure of bacterial communities. However, the reshaping effects on bacterial communities by the two algae differed significantly. Overall, the vertically transported phytoplankton in the seamount area not only contribute importantly to carbon sequestration via biological pump, but also may have an important reshaping effect on the bacterioplankton community structure in different water layers.